EFEKTIVITAS REALISASI ANGGARAN BIDANG PENYELENGGARAAN PEMERINTAHAN DESA - Kurniasari, Rita; Anam Miftakhul , Huda; Diana, Elvianita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2018)
The Village Fund Allocation is a part of the central and regional equity funds devoted to villages in implementing government services and community empowerment. In carrying out its duties the village government is required to run the wheels of government efficiently and effectively. This study aims to determine the level of effectiveness of budget realization of Village Fund Allocation in the implementation of village government in Jajar Village, Talun sub-district, Blitar regency in 2017. Data collected by observation method, library research, and interview. Data analysis uses effectiveness and effectiveness ratio. The results of research on the effectiveness of budget realization is at 90% -100% level and included in the effective category. Level of effectiveness of budget realization Village Fund Allocation in the implementation of village government in Jajar Village in 2017 (97.6%). This means that Jajar Village Government has optimized revenue or acceptance in applying the realization of budget ceiling of Village Fund Allocation in the administration of village government by doing priority scale in determining expenditure budget to fit with expectations and objectives as well as benefits for quality in budget realization.